Study guides

☆☆

Q: How do you simplify 2x plus 4x plus 3?

Write your answer...

Submit

Still have questions?

Related questions

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

4x plus 3 plus 2x is equivalent to expression 6x plus 3.

-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]

If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.

2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10

2x = 4x + 3 -2x = 3 x = -3 / 2

(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3

Lets simplify the above given equation : -8 plus 6(-x - 3) plus 4x simplified as : -8-6x -18 +4x =-2x -26 . =-2(x+13).

2x - 4x + 3 = 0 -2x + 3 = 0 2x = 3 x = 3/2 = 1.5

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

People also asked